Investments in "Green" Construction as a Foundation for the Innovative Development of the Construction Industry - KRYSHTAL, Halyna; KHIMICH, Sviatoslav; BRIUKHOVETSKA , Iryna (Ways to Improve Construction Efficiency, 2024)
The authors of the article investigate the role of investments in "green" construction as a key factor for the innovative development of the construction industry. Given the growing relevance of environmental issues in today’s world and increasing demands for sustainable development, the article analyzes the impact of investments in eco-friendly construction projects on the efficiency of resource utilization, ecological sustainability, and the competitiveness of enterprises. The study covers various aspects of "green" construction, including its impact on economic efficiency, social responsibility, and the opportunities for companies to secure leadership positions in the market. It is clarified that investments in ecologically certified construction projects allow companies to access new markets, particularly those with high environmental standards regulated through tax incentives, subsidies, and other state support mechanisms. Such investments not only reduce operating costs of facilities but also ensure a high quality of life for end consumers, making these properties attractive to both investors and clients. The study reveals that eco-friendly buildings can significantly increase property value in the market due to reduced operating costs and high energy efficiency. This, in turn, promotes investment returns and financial stability for companies undertaking such projects. Additionally, the presence of "green" building certification enhances the competitiveness of enterprises, enabling them to gain advantages in global markets, where environmental standards play a crucial role in selecting partners and suppliers. It is proven that investments in "green" construction are not only economically advantageous but also strategically important for the development of the industry in conditions of high competition and global environmental challenges. They ensure the sustainable development of companies, reduce their ecological footprint, and improve social responsibility. The authors propose, in particular, to strengthen state support for ecological construction through mechanisms such as subsidies, tax incentives, and grants to encourage the transition to eco-friendly technologies. They also recommend that companies actively integrate innovative solutions to conserve resources, improve energy efficiency, and reduce building operating costs, which will strengthen their market positions and ensure the long-term development of the industry as a whole.